Small Indigenous Fish species diversity, conservation and their importance in Koshi Province, Nepal - Yadav, Prakash Kumar; Subba, Bharat Raj (Our Nature, 2024)
Small Indigenous Fish Species (SIS) on the smaller side play a crucial role in aquatic ecosystems, offering valuable nutrients such as Omega-3 fatty acids, Vitamin A, and critical elements like Calcium, Phosphorus, and Iron that sustain human life. Unfortunately, their habitats are being destroyed by climate change and human activities, which possess a significant threat to SIS. In Koshi Province , Nepal, a two-year survey of SIS recorded 114 species belonging to 8 orders and 25 families.This paper focuses on the diversity, ecosystem services, economic importance,s status and aesthetic values of SIS.